Материнська О. В. Типологія найменувань частин тіла - Манакін, В.; Козлова, Т. (Мовознавство, 2010)
Рецензія на книгу: Материнська О. В. Типологія найменувань частин тіла. Умань : Софія, 2008.— 280 с.